Social Marketing of Electronic Coupons Under the Perspective of Social Sharing Behavior - Shia, An Shin; Chang, Kuei-Feng; Huang, Yu-Huang (Frontiers in Psychology, 2021)
This study aimed to (1) explore the correlated influential factors that promote consumers' sharing behaviors of electronic coupons, (2) identify relevant knowledge gaps on e-coupon sharing, and (3) develop a theoretical model to explain the e-coupon sharing behavior of consumers. This study suggested that familiarity and professionalism of the referral source have significant and positive impacts on the feeling of credibility of e-coupons, which promote consumers' willingness to share. Moreover, this research used electronic coupons as the product from (1) the concept of social marketing and (2) the perspective of the social sharing behavior of consumers. The research findings of this study showed that (1) community-based social marketing is covered in the social norm as social individuals frequently hope to share benefits with others. (2) People's sharing purpose is to promote their established social relationship via sharing the benefits to others. In this case, benefits referred to advantageous products' attributes and values consumers found on the products such as credibility of the products. (3) The interlaced display of products and social psychology in the field of social marketing was also discussed in this study. In short, the research results of this study theoretically contributed to indicate the connection mechanism between (A) social benefit-sharing behavior and (B) product benefits. That is to say, the feeling of credibility and willingness to shares are covered by the social benefit-sharing behavior mechanism, while the product-benefit mechanism covers professionalism, feeling of credibility and willingness to share. Note that the (A) social benefit-sharing behavior mechanism works in the form of social norms in sharing benefits to an individual's social networks; the (B) product-benefit mechanism work in the form of product values and attributes.